The implementation of total quality management (TQM) in housekeeping department of W Bali-Seminyak: A case study in housekeeping department - Yasa, I Ketut (International research journal of management, IT and social sciences, 2019)
Competition in the business field is rapid and tight, particularly in the hospitality industry. A company needs the efforts to do continuous improvement toward the potential of human resources, process, and the environment to bring about the best quality of product or service. The effective and efficient way to improve those capabilities is by implementing Total Quality Management (TQM). TQM contributes the benefit such as increasing the competitiveness of the company. TQM concept denotes the concept of continuous improvement that applies to every level of the operation. W Bali – Seminyak, specifically housekeeping department has objective to offer the unique and special moments, inventing the creative staff, and recultivating the hospitality in Bali which committed to implementing TQM optimally. The purpose of the study was to investigate the implementation of Total Quality Management in the housekeeping department of W Bali-Seminyak as well as the obstacles to it. Methods of analysis used in this study were descriptive qualitative and descriptive statistical analysis. The result of this study indicated TQM had been implemented in the housekeeping department, W Bali- Seminyak.